The Influence Of Return On Assets (ROA), Current Ratio (CR), and Debt-to-Equity Ratio (DER) On Stock Prices at PT. Unilever Indonesia Tbk Period 2014-2023 - Juanda, Ujang; Sudaryo, Yoyo; Ali, Mochammad Mukti (Jurnal sosial dan sains, 2025)
The capital market plays a crucial role in economic growth, serving as a platform for investors and companies to engage in financial transactions. One of the key factors investors consider when making investment decisions is stock price movement, which various financial ratios can influence. This study examines the effect of Return on Assets (ROA), Current Ratio (CR), and debt-to-equity ratio (DER) on stock prices at PT. Unilever Indonesia Tbk over the period 2014-2023. This research employs a quantitative method with a descriptive and verification approach, utilizing secondary data from the company's financial reports and stock price data from the Indonesia Stock Exchange (IDX). The purposive sampling method was used to select data, and analysis was conducted using multiple linear regression. The study also conducted classical assumption tests, including normality, heteroscedasticity, multicollinearity, and autocorrelation tests, to ensure the validity of the results. The findings reveal that ROA, CR, and DER do not significantly affect stock prices, either partially or simultaneously. This contradicts several previous studies that suggested a strong correlation between financial ratios and stock prices. The results indicate that stock price fluctuations at PT. Macroeconomic conditions, market sentiment, and external shocks may influence Unilever Indonesia Tbk. In conclusion, this study suggests that investors should consider additional factors beyond financial ratios when investing in the Fast Moving Consumer Goods (FMCG) sector. Future research should explore the impact of external factors, including inflation, interest rates, and industry trends, on stock price movements.